Innovation, industry equilibrium, and discount rates - Maria Cecilia Bustamante; Francesca Zucchi (European Central Bank (ECB), 2023)
We develop a model to examine how discount rates affect the nature and composition of innovation within an industry. Challenging conventional wisdom, we show that higher discount rates do not discourage firm innovation when accounting for the industry equilibrium. Higher discount rates deter fresh entry-effectively acting as entry barriers-but encourage innovation through the intensive margin, which can lead to a higher industry innovation rate on net. Simultaneously, high discount rates foster explorative over exploitative innovation. The model rationalizes observed patterns of innovation cyclicality, and predicts that lower entry in downturns hedges innovating incumbents against higher discount rates.
Keywords: G31; G12; O31; 330; Vertical and horizontal innovation; creative destruction; time-varying discount rates; risk premia